Delta tocotrienol in recurrent ovarian cancer. A phase II trial. (March 2019) - Thomsen, Caroline Brenner; Andersen, Rikke Fredslund; Steffensen, Karina Dahl; Adimi, Parvin; Jakobsen, Anders
Graphical abstract: Abstract: Delta tocotrienol has anti-neoplastic activity as demonstrated in several in-vitro and in-vivo investigations. The effect relies on inhibition of different pathways. It also has antiangiogenic activity, and an additive effect to bevacizumab may be expected. The present study was a phase II trial of bevacizumab combined with tocotrienol in chemotherapy refractory ovarian cancer. The study also included analysis of circulating tumor specific HOXA9 methylated DNA (HOXA9 meth-ctDNA) during treatment. The study included 23 patients. The rate of disease stabilization was 70% with very low toxicity. The median PFS was 6.9 months and the median OS 10.9 months, which is rather high compared to the current literature. A division of the patients according to level of HOXA9 meth-ctDNA already after the first cycle of chemotherapy resulted in two groups of patients with different prognoses. Patients with an increasing level of HOXA9 meth-ctDNA had a median PFS and OS of 1.4 and 4.3 months, respectively, compared to 7.8 and 12 months in the group with stable or decreasing levels. The combination of bevacizumab and tocotrienol is potent in chemotherapy refractory ovarian cancer. The level of HOXA9 meth-ctDNA after one cycle of chemotherapy holds important prognostic information.